RGO/TiO2 nanosheets immobilized on magnetically actuated artificial cilia film: a new mode for efficient photocatalytic reaction. Issue 17 (7th February 2017) - Wang, Wei; Huang, Xiaogu; Lai, Min; Lu, Chunhua
Abstract : Exploring a proper mode for practical reaction and efficient recycle has been an extensively studied subject in the photocatalysis field. Abstract : Exploring a proper mode for practical reaction and efficient recycle has been an extensively studied subject in the photocatalysis field. Powder suspension reaction systems and two-dimensional (2D) film reaction systems are insufficient to attain this goal. Herein, we report a systematic study on immobilizing anatase TiO2 nanosheets on the magnetically actuated artificial cilia film by employing reduced graphene oxide (RGO) as the contact medium. The three-dimensional (3D) artificial cilia film is efficient in immobilizing more powder photocatalysts. When the artificial cilia film is actuated by the rotating magnetic field, the rhodamine B (RhB) degradation efficiency can be greatly improved because of the enhanced mass transfer and product desorption efficiencies. Compared to the static state, a three-fold improvement of the photocatalytic activity is obtained when the magnetic field actuation speed is 800 rpm. Furthermore, 83.1% of the photocatalytic activity is retained after 15 circular reactions, indicating its relative stability. Moreover, RGO conductivity and Au surface plasma resonance (SPR) can further improve the RhB degradation efficiency of 9.0% and 8.8%, respectively. Our findings suggest that this new photocatalysis mode is helpful to apply to, and recycle, the high-reactivity powder photocatalysts.